(untitled) (Książnica Śląska, 2025)
The article is devoted to folk songs from the period of the Silesian Uprisings and the Plebiscite which were collected by professor Adolf Dygacz – ethnomusicologist, folklorist and publicist. The lyrics were created spontaneously to fit popular melodies, within the years 1919– 1922. They were printed in local newspapers, such as „Powstaniec” and „Kocynder”, songbooks (Śpiewnik powstańczy by Jan Eichorn, 1921; Pieśni powstańców górnośląskich by Jan Rzymełka, 1921) and leaflets. Nowadays, they are an important document of that period of history and its social moods. The article concentrates on analysis of eight folk songs, that are available on an album titled Nadstawcie ucha kochani ludkowie released by the author of this article. One of the ballads, Kajze się podzioł moj synocek miły? was used in a symphony by Henryk Mikołaj Górecki and Sól Ziemi Czarnej [Salt of the Black Earth], a film directed by Kazimierz Kutz.